2015
DOI: 10.1038/npp.2015.169
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-Like Phenotype Inherited by the F2 Generation of a Gestational Disruption Model of Schizophrenia

Abstract: Both environmental and genetic factors contribute to schizophrenia; however, the exact etiology of this disorder is not known. Animal models are utilized to better understand the mechanisms associated with neuropsychiatric diseases, including schizophrenia. One of these involves gestational administration of methylazoxymethanol acetate (MAM) to induce a developmental disruption, which in turn produces a schizophrenia-like phenotype in post-pubertal rats. The mechanisms by which MAM produces this phenotype are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 63 publications
(83 reference statements)
11
42
0
Order By: Relevance
“…In our previous publication, 16 we reported on 181 genes (representing upstream and downstream genes of 92 DMRs). Although the updated rat genome and our alternate analysis protocol increased the number of DMRs detected, there was high concordance between DMRs identified in our previous publication and those identified here; 71% of the DMRs representing upstream and downstream genes in our initial study had overlapping DMRs that were also detected here, all of these showed the same direction of effect (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous publication, 16 we reported on 181 genes (representing upstream and downstream genes of 92 DMRs). Although the updated rat genome and our alternate analysis protocol increased the number of DMRs detected, there was high concordance between DMRs identified in our previous publication and those identified here; 71% of the DMRs representing upstream and downstream genes in our initial study had overlapping DMRs that were also detected here, all of these showed the same direction of effect (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…16 The NEBNext Ultra TM DNA Library Prep Kit for Illumina was used to perform end repair, adapter ligation, and sample cleanup without size selection on 1 μg Covaris sheared DNA, according to the manufacturers’ protocol (starting volume 50 μl sheared DNA and 5.5 μl buffer EB). Unmethylated adapters (undiluted) obtained from the NEBNext Multiplex Oligos for Illumina Kit allowed for multiplexing of samples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations